Chromosome integrity : a major determinant of mitotic cell death in cancer treatment - Lai, Soak Kuan (2011)
Mitotic cell death is a major cell death pathway that occurs in cancer cells which have been treated with chemotherapeutic drugs. However, the mechanisms underlying this form of cell death is poorly understood. Here, a novel molecular event that regulates mitotic cell death is reported. During prolonged mitotic arrest, caspase-3 is activated and it cleaves condensin I subunit, Cap-H. Absence of Cap-H on the chromosomes compromises chromosome integrity, making them susceptible to degradation by caspase-activated DNase. When a caspase-resistant form of Cap-H is expressed in cells, mitotic chromosomes are able to maintain their structural integrity during mitotic arrest and thus, able to withstand nuclease cleavage. Taken together, this study provides new insights into the molecular events that regulate mitotic cell death.